PENGARUH FAKTOR PRIBADI TERHADAP MINAT MENABUNG NASABAH DI BANK SYARIAH - RONI ANDESPA (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2017)
The research theme is the financial and banking institutions. The research objectives are: 1) To measure the influence of personal factors on the variable interest in saving partially. 2) To measure the influence of variable personal factors on the variable interest in saving simultaneously. The object of research is sharia bank in West Sumatra. The research variables are personal factors and interest in saving. This research is quantitative research. The population is all customers of sharia banks in West Sumatra. The sample was 250 people. Data analysis using multiple linear regression analysis. The result of the research is: there is significant influence between the personal factor variable with the interest of saving.